Major incident medical management and support : the practical approach to pre-hospital incident command - Mackway-Jones, Kevin; Advanced Life Support Group (Manchester, England) (Chichester, West Sussex, UK : Wiley-Blackwell, 2012)
Includes bibliographical references and index